The relevance of IT and ICT in the effective management required for the allocation of resources essential to implementing the Ugandan Universal Primary Education program. - Agbonlahor, George Osemwengie Jr (2009)
This project examines the process of planning, management and allocation of resources required for the implementation of the Ugandan Universal Primary Education program. It commences with an introduction to the UPE program along with a detailed highlight of major education statistics in Uganda. It also highlights the importance of the UPE and aligns it with the global and in-country millennium development goal aimed at ensuring that the world’s children are able to complete a full course of primary schooling by 2015.